PENGARUH LINGKUNGAN KERJA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PT. KIMIA FARMA PLANT SEMARANG - Nugroho, Burhan; Hidayat, Wahyu; Suryoko, Sri (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aimed to determine the effect variables work environment, leadership and compensation of  PT.Kimia Farma Plaant Semarang’s employees' job satisfaction. This paper  is explanatory research. The sampling technique uses non-probability sampling technique with saturated sampling type that used as a sample that is 95 people. The data analysis technique used is simple linear regression analysis and multiple linear regression analysis with SPSS for windows version 16:00 The conclusion of this research is 55.8% of the respondents said the work environment is fair, 66.3% of respondents said leadership is fair, 91.6% of respondents said compensation in either category, and 67.4% of respondents stated to have job satisfaction tinggi.Work environment variable affect the job satisfaction of 25.1%. Leadership variables affect job satisfaction of 16.6%. Variable compensation affects the job satisfaction of 16.1%. Simulteously  the work environment, leadership and compensation affects job satisfaction by 36.1%. This means better work environment, leadership and compensation expected higher level employees' job satisfaction Based on the results the company needs to improve the quality of existing employment facilities such as keeping all existing work by organizing community service, to promote cooperation and liaison between the leadership of the employee gatherings are held regularly, compensation has created a well should be maintained so that the satisfaction increased employee and employee performance the better